2020
DOI: 10.1002/ejoc.202000386
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Peresters

Abstract: Peresters have long been familiar as radical initiators, oxidants for allylic functionalization, and as sources of electrophilic oxygen. In recent years, peresters have emerged as important reagents or intermediates for many additional reactions or processes, including C-H activation, dehydrogenative coupling, and activation of transition metal catalysts. This compre

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 295 publications
(308 reference statements)
0
19
0
Order By: Relevance
“…28 Moreover, derivatives can be easily accessed by standard acylation chemistry. 28 Nucleophilic addition to perester electrophiles can occur through two different pathways: (i) 1,2-addition at the carbonyl group and (ii) 1,4-addition to the peroxy oxygen. 28 Previous studies on the nucleophilic addition of amines to TBPB demonstrated that the C-attack (1,2-addition) predominates over the corresponding O-attack (1,4-addition).…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…28 Moreover, derivatives can be easily accessed by standard acylation chemistry. 28 Nucleophilic addition to perester electrophiles can occur through two different pathways: (i) 1,2-addition at the carbonyl group and (ii) 1,4-addition to the peroxy oxygen. 28 Previous studies on the nucleophilic addition of amines to TBPB demonstrated that the C-attack (1,2-addition) predominates over the corresponding O-attack (1,4-addition).…”
mentioning
confidence: 89%
“…The extrapolation of this method to hydroxylamine formation was attractive considering that TBPB is commercially available and employed in oxidations. 28 Moreover, derivatives can be easily accessed by standard acylation chemistry. 28 Nucleophilic addition to perester electrophiles can occur through two different pathways: (i) 1,2-addition at the carbonyl group and (ii) 1,4-addition to the peroxy oxygen.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“… 15 Widely used phthalimide-derived esters 16 containing an O–N bond proved to be unreactive, but peresters containing an O–O bond turned out to be much more satisfactory. 17 Herein, we describe the chemo- and stereoselective Cα alkylation of titanium(IV) enolates from chiral N -acyl oxazolidinones with tert -butyl peresters from branched aliphatic carboxylic acids, which permits the stereocontrolled introduction of secondary and tertiary alkyl groups with moderate to high yields ( Scheme 1 ). Importantly, this method gives a straightforward access to enantiomerically pure intermediates that can be employed as precursors for ligands in catalytic and asymmetric synthesis.…”
mentioning
confidence: 99%